2014
DOI: 10.1007/s00253-014-5608-8
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Monascus biology at the genetic level

Abstract: The genus of Monascus was nominated by van Tieghem in 1884, but its fermented product-red mold rice (RMR), namely red yeast rice, has been used as folk medicines, food colorants, and fermentation starters for more than thousands of years in oriental countries. Nowadays, RMR is widely developed as food supplements around the world due to its functional compounds such as monacolin K (MK, also called lovastatin) and γ-aminobutyric acid. But the usage of RMR also incurs controversy resulting from contamination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 109 publications
0
55
0
Order By: Relevance
“…The biosynthesis of Monascus pigments follows the polyketide pathway (Hajjaj et al 1997; Shao et al 2014). MpPKS5 and mppD are the structural genes of Monascus pigments and encode the polyketide synthases which are keys to the biosynthesis the polyketide chromophore of these pigments.…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthesis of Monascus pigments follows the polyketide pathway (Hajjaj et al 1997; Shao et al 2014). MpPKS5 and mppD are the structural genes of Monascus pigments and encode the polyketide synthases which are keys to the biosynthesis the polyketide chromophore of these pigments.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a conversion among the yellow, orange and red Monascus pigments might involve the MpigE gene (Liu et al 2014; Shao et al 2014), although the biosynthesis pathway of pigment remains unclear or controversial (Yang et al 2015). It has been reported that pH plays an important role in regulating the pigment components (Shi et al 2015, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of Monascus spp, in producing red pigment may be improved further by the application of genetic engineering techniques or genomics levels due to the increasing demands of the industry for the development of natural pigments [128,129]. On top of that, with the current situation, the use of nutraceutical supplements such as Monascus fermented products by the communities is growing tremendously due to health concerns.…”
Section: Current Trends and Future Perspectivesmentioning
confidence: 99%